Pemanfaatan Abu Serabut Kelapa dan Serbuk Cangkang Telur Terhadap Kuat Tekan Beton - Hammam Rofiqi Agustapraja; Fahrul Irfan Syah (Jurnal Teknik, 2023)
Indonesia is the largest coconut fiber producing country in the world and has not been able to process it optimally. Egg shell waste is also one of the wastes that is often encountered because many food raw materials use eggs. This research was conducted to determine the value of the compressive strength of concrete with the addition of coconut fiber ash and eggshell powder as a substitute for cement and which of the percentages of 0%, 0.5%, and 1.5% added mixture has optimal compressive strength for concrete quality. K – 225 or equivalent to 19.3 MPa at 28 days of age. The method used in this study is an experimental method according to SNI 03-2834-2000 concerning Procedures for Making Plans for Normal Concrete Mixture. The results of this study revealed that the addition of coconut fiber ash and eggshell powder to the concrete mixture decreased the compressive strength compared to normal concrete but not significantly. The average compressive strength value of normal concrete is 19.58 MPa. Whereas the compressive strength of concrete with the highest added material is the percentage of 0.5% coconut fiber ash and 0.5% eggshell powder with an average compressive strength of 19.30 MPa.